New record of chewing lice Piagetiella titan (Menoponidae: Mallophaga) Isolated from buccal cavity of White Pelican Pelecanus onocrotalus in Thi-Qar province-Southern Iraq - Abd-Ali Mohammad , Zainab (University of Thi-Qar Journal of Science, 2019)
In the present study the oral cavity of white pelican Pelecanus oncrotalus (collected from Al-Sanaf marsh southern Thi-Qar province, Iraq) was examined in the Biology department / College of Education for Pure Science / Thi-Qar University. A total of 23 chewing lice (10 males and 13 females) were collected from the oral cavity of P. oncrotaus bird and identified as Piagetiella titan during microscopial examination.The aim of this study is to give detailed information about P. titan, which was first found in Pelicans in Iraq to contribute parasitological fauna of Iraq.